2023
DOI: 10.1080/15592294.2023.2202835
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of epigenome-wide association studies on pregnancy vitamin B12 concentrations and offspring DNA methylation

Abstract: Circulating vitamin B12 concentrations during pregnancy are associated with offspring health. Foetal DNA methylation changes could underlie these associations. Within the Pregnancy And Childhood Epigenetics Consortium, we meta-analysed epigenome-wide associations of circulating vitamin B12 concentrations in mothers during pregnancy ( n = 2,420) or cord blood ( n = 1,029), with cord blood DNA methylation. Maternal and newborn vitamin B12 concentrations were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…By treating vitamin B12 deficiency with supplements, it may be possible to improve cognitive function and attention control in people with ADHD. In addition, vitamin B12 plays a role in DNA synthesis and methylation, processes that are essential for proper brain development and function [75]. Therefore, ensuring adequate vitamin B12 levels through supplementation can promote optimal brain health and reduce the risk of neurodevelopmental disorders such as ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…By treating vitamin B12 deficiency with supplements, it may be possible to improve cognitive function and attention control in people with ADHD. In addition, vitamin B12 plays a role in DNA synthesis and methylation, processes that are essential for proper brain development and function [75]. Therefore, ensuring adequate vitamin B12 levels through supplementation can promote optimal brain health and reduce the risk of neurodevelopmental disorders such as ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has also suggested that vitamin B12 serum levels in pregnant women may play a role in the offspring’s epigenetics. However, this has not yet been linked with children’s health outcomes in any way [ 169 ].…”
Section: Micronutrientsmentioning
confidence: 99%
“…Maternal and newborn vitamin B 12 concentrations are associated with DNA methylation at multiple CpGs in offspring blood [60]. By contrast, acute vitamin B 12 supplementation can improve behavioral measures that are associated with depression-like behavior in mice [61]. The effects of folate and vitamin B 12 are thus related to Endocrine Journal Advance Publication epigenetic changes in the offspring (and probably in the next generation as well) owing to the accessibility of the DNA during early development.…”
Section: Prevention Of Transgenerational Transmission Of Disease Susc...mentioning
confidence: 99%